Cover Picture: Tuning the Photophysical Properties of Spirolactam Rhodamine Photoswitches (Isr. J. Chem. 3‐4/2021). Issue 3 (23rd April 2021) - Li, Bo; Haris, Uroob; Aljowni, Maha; Nakatsuka, Andrew; Patel, Shreya K.; Lippert, Alexander R.
Abstract : The cover art shows a fluorescent image of Peruna Mustang, the mascot of Southern Methodist University, demonstrating precise photoactivation of a spirolactam‐derived photoswitch. The method enables the generation of free‐floating three‐dimensional images in solution (see article by B. Li, A. R. Lippert et al., https://doi.org/10.1002/ijch.202000083).